Biodegradable paper diaper

By adopting the combination of porous polylactic fiber hot air non-woven fabric, polylactic fiber high fluffy diversion layer and spunlace non-woven fabric, the existing diapers are solved, and antibacterial and rapid Absorbent, dry and biodegradable diapers meet compostable degradability standards.

CN119280453AActive Publication Date: 2025-01-10CHANGSHU GOLD SPRING CHEM FIBERS & KNITTINGS +1

Patent Information

Application Number
CN202411410051.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The research and development of existing biodegradable diapers is deviated from reality, it is costly and difficult to achieve large-scale production on existing equipment, and there is a lack of biodegradable diapers with cost advantages and functionality.

Method used

Porous polylactic acid fiber hot air nonwoven fabric is used as the surface layer, combined with polylactic fiber high fluffy guide layer and spunlace nonwoven fabric as the absorbent core layer, and PHA modified polylactic acid film is used as the anti-seepage base film, through specific Spinning process and material ratios are used to prepare diapers with antibacterial, rapid infiltration, dryness and biodegradability.

Benefits of technology

It realizes natural weak acid antibacterial, rapid absorption, low reflux, dryness and biodegradability. At the same time, mass production is achieved on conventional equipment, reducing the content of non-degradable ingredients and meeting the standards of compostable degradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119280453A_ABST
    Figure CN119280453A_ABST
Patent Text Reader

Abstract

The invention discloses a biodegradable paper diaper which comprises a paper diaper body, leakage-proof side edges, hook-and-loop fasteners and an elastic waistline. The paper diaper body comprises a surface layer, an absorption core layer and an anti-seepage bottom film. The surface layer is a porous polylactic acid fiber hot air non-woven fabric, and the absorption core layer comprises an upper layer, a middle layer and a lower layer; the upper layer is dust-free paper, the middle layer is a polylactic acid fiber diversion layer containing biodegradable super absorbent resin, and the lower layer is a polylactic acid fiber spunlace non-woven fabric; and the impermeable bottom film is a PHA modified polylactic acid film. The faintly acid and natural antibacterial activity are detected and authenticated by authoritative institutions, so that the product is particularly suitable for processing disposable hygienic products such as paper diapers, sanitary towels, panty liners and the like. The polylactic acid fiber hot air non-woven fabric has the advantages of being high in infiltration speed, capable of dredging loose stool, dry, comfortable, breathable and soft. Various polylactic acid fiber non-woven fabrics are prepared and selected, and are matched with the high-water-absorption resin capable of being composted and degraded, so that the standards of composted degradation are completely met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a biodegradable diaper, belonging to the technical field of diapers. Background Art

[0002] The diapers on the current market mainly include three categories of products: baby diapers, adult diapers and pet diapers, among which baby diapers account for the largest proportion. According to the latest report "Global Baby Diaper Market Report 2023-2029" by the QYResearch research team, the global baby diaper market size is expected to reach US$48.85 billion in 2029, with a compound annual growth rate of 2.5% in the next few years. The main raw materials for making diapers are non-degradable plastics such as polyethylene, polypropylene, absorbent resin, and hot melt adhesive. According to the popular ultra-thin diapers in the market (that is, the composition materials are: surface hot air non-woven fabric, dust-free paper, fluffy hot air non-woven fabric, polymer, coating layer, hot melt adhesive and bottom film), the non-degradation rate of the materials used exceeds 90%. Therefore, from the perspective of the sustainable development of the ecological environment, it is very important to research and develop compostable diapers and reach the level of large-scale production, which is very important for the sustainable development of the environment and the benefit of future generations.

[0003] However, judging from the existing information, the current research and development of biodegradable diapers deviates from reality and is merely conducted in laboratories. The preparation methods and materials used are very expensive and difficult to scale up using existing equipment. Therefore, it is very important to develop and produce biodegradable diapers that have cost advantages, can be mass-produced on existing equipment, and have certain functionality. Summary of the invention

[0004] The object of the present invention is to provide a biodegradable diaper having antibacterial and biodegradable properties.

[0005] To solve the above technical problems, the purpose of the present invention is achieved as follows:

[0006] The biodegradable diaper of the present invention comprises a diaper body, leak-proof side edges, Velcro and an elastic waist; the diaper body comprises a surface layer, an absorbent core layer and an impermeable bottom film;

[0007] The surface layer is a porous polylactic acid fiber hot air nonwoven fabric, and the absorbent core layer includes an upper layer, a middle layer and a lower layer; the upper layer is dust-free paper, the middle layer is a polylactic acid fiber guide layer containing a biodegradable super absorbent resin, and the lower layer is a polylactic acid fiber spunlace nonwoven fabric;

[0008] The anti-seepage bottom membrane is a PHA modified polylactic acid membrane.

[0009] On the basis of the above scheme and as a preferred scheme of the above scheme: the PLA:PHA ratio in the PHA modified polylactic acid film is 3-7:7-3.

[0010] On the basis of the above scheme and as a preferred scheme of the above scheme: the polylactic acid fiber hot air non-woven fabric is composed of low melting point polylactic acid fiber and high and low melting point polylactic acid fiber mixed in a weight ratio of 25-45:55-75, wherein the low melting point polylactic acid fiber has a specification of 1.5-3.0D*38mm, and the high and low melting point polylactic acid fiber has a specification of 1.0-2.0D*38mm; the core layer of the high and low melting point polylactic acid fiber is a high melting point polylactic acid component, and the skin layer is a low melting point polylactic acid component or a modified polylactic acid component; the low melting point polylactic acid fiber is a modified polylactic acid component.

[0011] On the basis of the above scheme and as a preferred scheme of the above scheme: the modified component used in the modified polylactic acid component includes at least one of PHA, PBT, PBS, PBAT or PCL.

[0012] On the basis of the above scheme and as a preferred scheme of the above scheme: the preparation process of the polylactic acid fiber hot air non-woven fabric is as follows:

[0013] When opening, the beater speed of the cotton opener is controlled to be 250-380r / min. During the mixing process, the cotton is mixed by horizontal spreading and direct taking. When discharging cotton, the speed of the cotton roller is controlled to be between 180-220r / min. During fine opening, the speed of the cotton opener is controlled to be 550-680r / min. In the airflow feeding process, the air pressure of the air box is controlled to be between 3-4.8MPa, and the speed of the mixing roller of the air box is controlled to be between 310-430r / min. The speed of the cotton outlet roller is 18.2-25.5 rpm. During the carding process, the cylinder line speed is adjusted to 610-750m / min, the working roller line speed is controlled to 42.5-58.9m / min, the stripping roller line speed is 120.3-141.2m / min, and the doffer speed is controlled to 20.5-30.6m / min. The weight of the single-layer fiber web formed after stripping by the condensing roller and the stripping roller is 9.8-15.4g / m2. The shaping process is carried out in a four-stage flat-net oven, and the shaping temperatures of the four-stage oven are controlled at 100-110 degrees, 125-135 degrees, 120-130 degrees, and 110-120 degrees respectively. The running speed of the fiber web in the oven is 70-80mi / min. After leaving the oven, a polylactic acid fiber hot air non-woven fabric with a gram weight of 19.6-30.8g / m2 is obtained, which is composed of low-melting-point polylactic acid fibers and high and low-melting-point polylactic acid fibers.

[0014] On the basis of the above scheme and as a preferred scheme of the above scheme: the preparation process of the absorbent core layer is as follows:

[0015] First, the polylactic acid spunlace nonwoven fabric used in the lower layer is unwound, and a layer of a mixture of high and low melting point polylactic acid fibers and super absorbent resin is sprayed on it, with a spraying amount of 30-50 g / m2, wherein the ratio of high and low melting point polylactic acid bicomponent fibers: super absorbent resin is: 0.5-1.5:98.5-99.5, wherein the particle size of super absorbent resin is 80-90 mesh;

[0016] The polylactic acid fiber high-loft guide layer material is unwound and laid on the surface of the high-low melting point polylactic acid fiber and super absorbent resin mixture, and then the super absorbent resin is sprayed thereon, and the spraying amount is 70-80 g / m2, wherein the particle size of the super absorbent resin is 60-70 meshes, and the sprayed lower layer of polylactic acid spunlace non-woven fabric and the polylactic acid fiber high-loft guide layer are sent together to the upper and lower reciprocating vibration conveying long curtains driven by the transmission device, and the conveying long curtain is driven by the eccentric mechanism driven by the motor to generate an exciting force to generate vibration, and the vibration intensity can be controlled in the range of 3-6, and the vibration frequency that can be generated is 25-30Hz, and the amplitude is 2-4mm, so that the sprayed super absorbent resin is better dispersed in the polylactic acid fiber high-loft guide layer;

[0017] After exiting the vibrating conveyor curtain, a layer of high-low melting point polylactic acid double fiber and super absorbent resin mixture is sprayed again on the surface of the polylactic acid fiber high-loft guide layer, with a spraying amount of 15-30 g / m2, wherein the ratio of high-low melting point polylactic acid fiber: super absorbent resin is 50:50, and the particle size of super absorbent resin is 30-40 mesh;

[0018] Finally, the dust-free paper is unrolled as the upper layer of the absorbent;

[0019] The three layers after stacking are put into the oven together for heat setting and reinforcement. A three-stage flat-net oven is used. The heating temperature in the first stage oven is controlled to be 110-120°C, the heating temperature in the second stage oven is controlled to be 120-140°C, and the heating temperature in the third stage oven is controlled to be 110-120°C. After exiting the oven, a three-layer absorption layer is obtained with a gram weight of 180-240 g / m2.

[0020] The polylactic acid fiber spunlace nonwoven fabric has a gram weight of 30-40g / m2, and the polylactic acid fiber used is a water-repellent fiber with a surface oil content of 0.06-0.08%. The melting point of the high-melting-point polylactic acid fiber is 160-175 degrees.

[0021] On the basis of the above scheme and as a preferred scheme of the above scheme: during the spinning process of the low melting point polylactic acid fibers and the high and low melting point polylactic acid fibers, Lurol PP-14160 type hydrophilic oil agent is added to the surface oil agent used.

[0022] On the basis of the above scheme and as a preferred scheme of the above scheme: the surface oil content of the low melting point polylactic acid fiber is 0.02-0.08%, and the surface oil content of the high and low melting point polylactic acid fiber is 0.12-0.15%.

[0023] Compared with the prior art, the biodegradable diaper prepared by the present invention has the following beneficial effects:

[0024] 1) Natural weak acidity and antibacterial properties

[0025] Polylactic acid (PLA) fiber is an environmentally friendly biomass material. In addition to its biodegradability, it also has a weakly acidic fiber surface, natural antibacterial and deodorizing functions. Its weak acidity and natural antibacterial properties have been tested and certified by authoritative organizations, making it particularly suitable for processing disposable sanitary products such as diapers, sanitary napkins and panty liners.

[0026] 2) Fast infiltration speed and good dryness

[0027] The surface layer of the diaper of the present invention adopts a hot air nonwoven fabric composed of low-melting point single-component polylactic acid fiber and high-low melting point polylactic acid bicomponent fiber. Since the low-melting point single-component polylactic acid fiber has a low crystallinity, it is very easy to shrink during the heating process, and then pull and involve the surrounding high-low melting point polylactic acid bicomponent fiber, forming countless pores inside the fiber net. As the content of low-melting point single-component polylactic acid fiber increases, the porosity of the fiber net increases, greatly improving the pore structure of the fiber net. At this time, the high-low melting point polylactic acid bicomponent fiber not only serves as the skeleton of the fiber net, but also plays a role in bonding and fixing the low-melting point single-component polylactic acid fiber. In combination with the regulated hot air production process, a polylactic acid fiber hot air nonwoven fabric containing multiple pores was successfully prepared. Since the surface moisture regain of the polylactic acid fiber is only about 0.4%, the prepared polylactic acid fiber hot air nonwoven fabric has the characteristics of fast infiltration speed, can dredge loose stools, dry, breathable and soft.

[0028] 3) Fast absorption and low back permeability

[0029] The absorbent core layer of the present invention uses the patented high-loft polylactic acid fiber guide layer as the main absorbent material. Its high loftiness and guide property provide a good carrier for dispersing and wrapping the super absorbent resin. At the same time, its unique high water conductivity can quickly guide the liquid transmitted from the surface layer to the surrounding super absorbent resin, avoiding the blockage caused by local super absorbent resin absorption saturation, providing it with sufficient swelling space for liquid absorption, so that the absorption capacity of the super absorbent resin can be fully utilized, thereby reducing the use of super absorbent resin and reducing production costs; on the other hand, it also eliminates the need for hot melt adhesive to bond and fix the super absorbent resin in the core of traditional diapers, further reducing the content of non-degradable components in diapers.

[0030] 4) Processability of conventional equipment

[0031] All non-woven fabric materials used in the diapers of the present invention, the surface layer 100% polylactic acid fiber hot air non-woven fabric, the dust-free paper containing polylactic acid fibers in the middle absorption layer, the high-degradation rate and high-fluff polylactic acid fiber guide layer, the polylactic acid fiber spunlace non-woven fabric, and the polylactic acid spunbond non-woven fabric can all be successfully produced on existing conventional equipment. At the same time, they all have manufacturers and have fully reached the scale of mass production. The downstream market clients need to be developed in the future.

[0032] 5) Biodegradability

[0033] Due to the complex structure of diapers, including many kinds of materials, it is very difficult to truly achieve biodegradability. Even so, through the calculation of diaper materials, it can be known that among all the materials that make up diapers (surface non-woven fabric, middle absorbent core layer, anti-seepage bottom film, anti-leakage edge, hot melt adhesive, Velcro and elastic waist), the absorbent core layer accounts for 55.06%, the surface non-woven fabric, bottom anti-seepage film, elastic waist non-woven fabric and anti-side leakage edge non-woven fabric account for 34.44%. In ordinary thin baby diapers, the absorbent core layer and various non-woven fabrics account for 89.5%, while the remaining hot melt adhesive, front waist tape, elastic waist elastic band, leg elastic band and three-dimensional protective elastic band, magic buckle and left and right non-woven fabrics account for only 10.5%. Therefore, the present invention prepares and selects a variety of polylactic acid fiber non-woven fabrics, combined with compostable and degradable super absorbent resin (ISO14855: 180-day biodegradability ≥ 60%), which fully meets the compostable and degradable standards.

[0034] Biodegradable super absorbent resin (the biodegradation rate of Formosa Plastics Corporation's BC706 biodegradable super absorbent resin is 66% (180 days). According to the EN 13432 and GB / T 20197 evaluation standards, the composting degradation rate or biodegradation rate of bio-based care products ≥ 60% can meet the degradation standard requirements). BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic diagram of the structure of the diaper body;

[0036] Figure 2 It is a cross-sectional structure diagram of high and low melting point polylactic acid fibers;

[0037] Figure 3 It is a longitudinal structure diagram of high and low melting point polylactic acid fibers;

[0038] Figure 4 This is a cross-sectional structure diagram of low melting point polylactic acid fiber;

[0039] Figure 5 It is a longitudinal structure diagram of low melting point polylactic acid fiber;

[0040] Figure 6This is a surface photo of the polylactic acid fiber hot air nonwoven fabric;

[0041] Figure 7 This is an electron microscope image of a polylactic acid fiber hot air nonwoven fabric;

[0042] Figure 8 It is a diagram of the absorbent core structure;

[0043] Fig. 9 The biodegradable diaper prepared by the present invention is in a three-folded state;

[0044] Fig.10 The biodegradable diaper prepared by the present invention is in an unfolded state;

[0045] Fig.11 This is the biodegradable diaper degradation experiment after four weeks;

[0046] Fig.12 It is the biodegradable diaper degradation experiment after six weeks;

[0047] Fig.13 It is the biodegradable diaper degradation experiment after eleven weeks;

[0048] Fig.14 It is the biodegradable diaper degradation experiment after twelve weeks;

[0049] Fig.15 It is the biodegradable diaper degradation experiment after thirteen weeks;

[0050] Fig.16 It is the relationship curve between carbon dioxide release rate (kg / ton / day) and time (week).

[0051] The markings in the figure are as follows: 1-surface layer; 2-absorbent core layer; 3-anti-seepage bottom film. DETAILED DESCRIPTION

[0052] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0053] Embodiment 1

[0054] The biodegradable diaper involved in this embodiment includes a diaper body, leak-proof sides, Velcro and an elastic waist; the diaper body includes a surface layer 1, an absorbent core layer 2 and an impermeable bottom film 3; the surface layer 1 is a porous polylactic acid fiber hot air non-woven fabric, and the absorbent core layer 2 includes an upper layer, a middle layer and a lower layer; the upper layer is dust-free paper, the middle layer is a polylactic acid fiber guide layer containing a biodegradable superabsorbent resin, and the lower layer is a polylactic acid fiber spunlace non-woven fabric; the impermeable bottom film 3 is a PHA-modified polylactic acid film.

[0055] The preparation method of the porous polylactic acid fiber hot air nonwoven fabric used in the surface layer 1 of this embodiment is as follows:

[0056] Ordinary hot air cotton production lines are used, such as the hot air cotton production line produced by Changshu Jiuyi High-tech Nonwoven Equipment Co., Ltd. The process flow is made of mixing, coarse opening, cotton blending, fine opening, airflow feeding, carding, web forming and heat setting. Among them, due to the low melting point of single-component polylactic acid fiber, in order to avoid the polylactic acid fiber melting and easy condensation into "corn kernels" and hard hand feel during the opening, carding and heat setting processes, the original PE / PP hot air non-woven fabric production opening, mixing, carding and setting processes are adjusted to reasonably regulate the longitudinal and transverse arrangement directions of the fibers in the fiber web, including various speed ratios of the cylinder and the working roller and stripping roller, the cylinder and the doffer, the condensing roller and the doffer during carding, the control of the draft ratio and the selection of the net quantity. A special process scheme of large gauge, low draft, low speed, light basis weight, weak combing, low tension and multi-stage shaping is adopted to further reduce excessive friction and thermal embrittlement of the fibers. The low-melting-point polylactic acid fibers and high- and low-melting-point polylactic acid fiber hot air non-woven fabrics produced have correct fiber arrangement direction, many pores and irregular pore distribution, and have a three-dimensional structure. The fiber mesh ensures the uniformity, thickness, basis weight and longitudinal and transverse strength ratio requirements of the fiber mesh. The low-melting-point polylactic acid fibers and high- and low-melting-point polylactic acid fibers are in a ratio of 25:75.

[0057] The main process parameters are as follows: the beater speed of the cotton opener is controlled at 380r / min during opening, the cotton is mixed by horizontal laying and direct taking during the mixing process, so as to achieve the purpose of fully mixing the low-melting-point polylactic acid fiber and the high- and low-melting-point polylactic acid fiber, the speed of the cotton roller is controlled between 220r / min during cotton discharge, the speed of the cotton opener is controlled at 680r / min during fine opening, the air pressure of the air cotton box is controlled between 4.8MPa during the airflow feeding process, the speed of the mixing roller of the air pressure cotton box is controlled between 430r / min, the speed of the cotton discharge roller is controlled at 25.5 rpm, the cylinder line speed is adjusted to 750m / min during the combing process, the working roller line speed is controlled to 58.9m / min, the stripping roller line speed is 141.2m / min, the doffer speed is controlled to 30.6m / min, and the weight of the single-layer fiber web formed after the condensation roller and the stripping roller stripping the web is 9.8g / m 2 The shaping process is carried out in a four-stage flat-net oven, and the shaping temperatures of the four-stage oven are controlled at 110°C, 135°C, 130°C, and 120°C respectively. The running speed of the fiber web in the oven is 80mi / min. After exiting the oven, a low-melting-point polylactic acid fiber and a high- and low-melting-point polylactic acid two-component fiber hot air nonwoven fabric with a gram weight of 19.6g / m2 are obtained.

[0058] Among the above, the low melting point single component polylactic acid fiber and the high and low melting point polylactic acid two-component fiber are specially developed and produced by Suzhou Jinquan New Materials Co., Ltd. The high and low melting point polylactic acid fiber cortex is a modified polylactic acid component, such as Figure 2 and Figure 4 As shown, the modified components include biodegradable materials such as PHA, PBT, PBS, PBAT, PCL, etc. The preferred modified component in the present invention is PHA+PBS. In addition, low melting point polylactic acid fiber is also a modified fiber, such as Figure 4 and Figure 5 As shown, the modified components include biodegradable materials such as PHA, PBT, PBS, PBAT, PCL, etc., and the preferred modified component is PHA, and the modified fiber ratio is PLA:PHA=95:5.

[0059] The melting point of the low-melting-point polylactic acid fiber is 118-135°C, the core layer of the high-low melting-point polylactic acid fiber is a high-melting-point polylactic acid component, wherein the melting point of the core layer is 160-175°C, and the skin layer is a low-melting-point component with a melting point of 118-135°C. The prepared polylactic acid fiber hot air nonwoven fabric is as follows Figure 6 and Figure 7 shown.

[0060] The absorbent core layer 2 comprises an upper layer, a middle layer and a lower layer. The upper layer is dust-free paper, the middle layer is a polylactic acid fiber guide layer containing biodegradable super absorbent resin, and the bottom layer is a polylactic acid fiber spunlace non-woven fabric.

[0061] The surface dust-free paper weight is 35g / m 2 The dust-free paper is heat-sealed dust-free paper, and the fiber ratio is: wood pulp fiber: high and low melting point polylactic acid fiber = 75:25, wherein the high and low melting point polylactic acid fiber is 3 mm long and has a curl of 0. The dust-free paper is produced by Jiaxing Shenxin Nonwoven Co., Ltd.

[0062] During production, first, the lower layer of polylactic acid spunlace nonwoven fabric is unrolled, and a layer of high-low melting point polylactic acid fiber and super absorbent resin mixture is sprayed on it, with a spraying amount of 30 g / m2, wherein the ratio of high-low melting point polylactic acid two-component fiber: super absorbent resin is: 0.5:99.5, wherein the particle size of super absorbent resin is 80 mesh; the polylactic acid fiber high-loft guide layer material is unrolled and laid on the surface of the high-low melting point polylactic acid fiber and super absorbent resin mixture, and then super absorbent resin is sprayed on it, with a spraying amount of 70 g / m2, wherein the particle size of super absorbent resin is 60 mesh, and the sprayed lower layer of polylactic acid spunlace nonwoven fabric and polylactic acid fiber high-loft guide layer are sent to the upper and lower driven by the transmission device together. On the reciprocating vibrating conveyor curtain, the conveyor curtain generates vibration through the exciting force generated by the eccentric mechanism driven by the motor, and the vibration intensity can be controlled within the range of 3, the vibration frequency that can be generated is 25Hz, and the amplitude is 2mm, so that the sprayed super absorbent resin can be better dispersed in the high-loft guide layer of the polylactic acid fiber; after exiting the vibrating conveyor curtain, a layer of high-low melting point polylactic acid two-component fiber and super absorbent resin mixture is sprayed again on the surface of the polylactic acid fiber high-loft guide layer, and the spraying amount is 15 grams / square meter, wherein the ratio of high-low melting point polylactic acid two-component fiber: super absorbent resin is: 50:50, wherein the particle size of the super absorbent resin is 30 mesh, and finally the upper layer of dust-free paper is unrolled as the surface layer of the absorbent.

[0063] The above three-layer composite body enters the oven together for heat setting and reinforcement. A three-stage flat-mesh oven is adopted. The heating temperature in the first stage oven is controlled to be 110°C, the heating temperature in the second stage oven is controlled to be 120°C, and the heating temperature in the third stage oven is controlled to be 110°C. After exiting the oven, a three-layer absorption layer is obtained with a gram weight of 180 g / m2.

[0064] The polylactic acid fiber spunlace nonwoven fabric has a gram weight of 30 g / m 2 The high melting point polylactic acid fiber used is a water-repellent fiber with a surface oil content of 0.06%. The melting point of the high melting point single-component polylactic acid fiber is 160-175 degrees.

[0065] For low melting point polylactic acid fiber and high and low melting point polylactic acid fiber, Lurol PP-14160 hydrophilic oil is specially added to the spinning oil during the spinning process, which has the function of single-point multiple hydrophilization and fast water penetration. The surface oil content of low melting point single component polylactic acid fiber is controlled to be 0.02%, and the surface oil content of high and low melting point polylactic acid two-component fiber is 0.12%. The different oil content is mainly to make the single component polylactic acid fiber produce better melt bonding in the subsequent processing process.

[0066] In the above, the polylactic acid fiber high-loft guide layer is a guide layer with an invention patent owned by Suzhou Jinquan New Materials Co., Ltd., specifically a guide layer material with a high degradation rate and a preparation method thereof, with patent authorization number: ZL201710096961.0. The super absorbent resin used in the absorbent core layer is a biodegradable absorbent resin of Formosa Plastics Corporation, model BC706, with a biodegradability rate of 66% (180 days). The absorbent core layer prepared is as follows Figure 8 shown.

[0067] The anti-seepage bottom film 3 is a composite film of polylactic acid fiber spunlace nonwoven fabric and a degradable polylactic acid modified film with polylactic acid as the main component, the modified component is PHA, PBHA, PBS, etc., preferably PHA, and the bottom film with polylactic acid as the main component is produced by Fujian Green Grid Biodegradable Co., Ltd. The weight of the polylactic acid fiber spunlace nonwoven composite film is 55 g / m2.

[0068] Since diapers are a composite of multiple materials, there are also non-woven fabrics for leakproof hems and elastic waistbands. The leakproof hems can be made of polylactic acid fiber spunlace non-woven composite film with a gram weight of 40 g / m2, and the non-woven fabrics for elastic waistbands are polylactic acid spunbond non-woven fabrics (polylactic acid spunbond non-woven fabrics are produced by Shanghai Jingfa Industrial Co., Ltd.) with a gram weight of 35 g / m2. Other components include hot melt adhesive, waist stickers, magic buckles and elastic bands, which can be ignored because they only account for about 10.5%.

[0069] The biodegradable diaper includes 100% polylactic acid fiber hot air nonwoven fabric, an absorbent core material with polylactic acid as the main component, a polylactic acid fiber spunlace nonwoven composite film, a polylactic acid leakproof separator and a polylactic acid spunbond nonwoven elastic waist. The above materials are processed by conventional diaper production equipment to form biodegradable diapers. The prepared diaper supplements such as Fig. 9 and Fig.10 As shown. Fig. 9 The length when folded is 145.4mm and the width is 100.5mm.

[0070] Embodiment 2

[0071] The biodegradable diaper involved in this embodiment includes a diaper body, leak-proof sides, Velcro and an elastic waist; the diaper body includes a surface layer 1, an absorbent core layer 2 and an impermeable bottom film 3; the surface layer 1 is a porous polylactic acid fiber hot air non-woven fabric, and the absorbent core layer 2 includes an upper layer, a middle layer and a lower layer; the upper layer is dust-free paper, the middle layer is a polylactic acid fiber guide layer containing a biodegradable superabsorbent resin, and the lower layer is a polylactic acid fiber spunlace non-woven fabric; the impermeable bottom film 3 is a PHA-modified polylactic acid film.

[0072] The preparation method of the porous polylactic acid fiber hot air nonwoven fabric used in the surface layer 1 of this embodiment is as follows:

[0073] Ordinary hot air cotton production lines are used, such as the hot air cotton production line produced by Changshu Jiuyi High-tech Nonwoven Equipment Co., Ltd. The process flow is made of mixing, coarse opening, cotton blending, fine opening, airflow feeding, carding, web forming and heat setting. Among them, due to the low melting point of single-component polylactic acid fiber, in order to avoid the polylactic acid fiber melting and easy condensation into "corn kernels" and hard hand feel during the opening, carding and heat setting processes, the original PE / PP hot air non-woven fabric production opening, mixing, carding and setting processes are adjusted to reasonably regulate the longitudinal and transverse arrangement directions of the fibers in the fiber web, including various speed ratios of the cylinder and the working roller and stripping roller, the cylinder and the doffer, the condensing roller and the doffer during carding, the control of the draft ratio and the selection of the net quantity. A special process scheme of large gauge, low draft, low speed, light basis weight, weak combing, low tension and multi-stage shaping is adopted to further reduce excessive friction and thermal embrittlement of the fibers. The low-melting-point polylactic acid fibers and high- and low-melting-point polylactic acid fiber hot air non-woven fabrics produced have correct fiber arrangement direction, many pores and irregular pore distribution, and have a three-dimensional structure. The fiber mesh ensures the uniformity, thickness, basis weight and longitudinal and transverse strength ratio requirements of the fiber mesh, among which the low-melting-point polylactic acid fibers and high- and low-melting-point polylactic acid fibers are in a ratio of 30:70.

[0074] The main process parameters are as follows: the beater speed of the cotton opener is controlled at 310r / min during opening, and the cotton is mixed by horizontal laying and direct taking during the mixing process, so as to achieve the purpose of fully mixing the low-melting-point single-component polylactic acid fiber and the high-low melting-point polylactic acid two-component fiber. The speed of the cotton roller is controlled between 197r / min when discharging cotton, and the speed of the cotton opener is controlled at 610r / min during fine opening. In the airflow feeding process, the air pressure of the air pressure cotton box is controlled at 4MPa, the speed of the mixing roller of the air pressure cotton box is controlled at 390-r / min, and the speed of the cotton discharging roller is controlled at 20.1 rpm. In the combing process, the cylinder line speed is adjusted to 790m / min, the working roller line speed is controlled to 50.3m / min, the stripping roller line speed is 132.1m / min, and the doffer speed is controlled to 25.6m / min. The weight of the single-layer fiber web formed after the condensation roller and the stripping roller stripping the web is 12.6g / m 2 The shaping process is carried out in a four-stage flat-net oven. The shaping temperatures of the four-stage oven are controlled at 105°C, 130°C, 125°C, and 115°C respectively. The running speed of the web in the oven is 75 m / min. The weight after leaving the oven is 25.2 g / m 2 Low melting point polylactic acid fiber and high and low melting point polylactic acid fiber hot air non-woven fabric.

[0075] In the above, the low melting point polylactic acid fiber and the high and low melting point polylactic acid fiber are specially developed and produced by Suzhou Jinquan New Materials Co., Ltd., wherein the high and low melting point polylactic acid two-component fiber cortex is a modified polylactic acid component, and the modified components include biodegradable materials such as PHA, PBT, PBS, PBAT, PCL, etc. The preferred modified component in the present invention is PHA+PBS. In addition, the low melting point single-component polylactic acid fiber is also a modified fiber, and the modified components include biodegradable materials such as PHA, PBT, PBS, PBAT, PCL, etc. The preferred modified component is PHA, and the modified fiber ratio is PLA:PHA=90:10.

[0076] Among them, the melting point of the low-melting point single-component polylactic acid fiber is 118-135°C, the core layer of the polylactic acid two-component fiber is the high-melting point polylactic acid component, wherein the melting point of the core layer is 160-175°C, and the skin layer is the low-melting point component, with a melting point of 118-135°C.

[0077] The absorbent core layer 2 comprises an upper layer, a middle layer and a lower layer. The upper layer is dust-free paper, the middle layer is a polylactic acid fiber guide layer containing biodegradable super absorbent resin, and the bottom layer is a polylactic acid fiber spunlace non-woven fabric.

[0078] The surface dust-free paper has a gram weight of 38g / m 2 The dust-free paper is heat-sealed dust-free paper, and the fiber ratio is: wood pulp fiber: high-low melting point polylactic acid bicomponent fiber = 80:20, wherein the high-low melting point polylactic acid bicomponent fiber is 4 mm long and has a curl of 0. The dust-free paper is produced by Jiaxing Shenxin Nonwoven Co., Ltd.

[0079] During production, first, the lower layer of polylactic acid spunlace nonwoven fabric is unrolled, and a layer of high-low melting point polylactic acid fiber and super absorbent resin mixture is sprayed on it, with a spraying amount of 40 g / m2, wherein the ratio of high-low melting point polylactic acid fiber: super absorbent resin is 1:99, and the particle size of super absorbent resin is 85 mesh; the polylactic acid fiber high-loft guide layer material is unrolled and laid on the surface of the high-low melting point polylactic acid fiber and super absorbent resin mixture, and then super absorbent resin is sprayed on it, with a spraying amount of 75 g / m2, wherein the particle size of super absorbent resin is 65 mesh, and the sprayed lower layer of polylactic acid spunlace nonwoven fabric and polylactic acid fiber high-loft guide layer are sent together to the upper and lower reciprocating driven by the transmission device On the vibrating conveyor curtain, the conveyor curtain generates vibration through the exciting force generated by the eccentric mechanism driven by the motor. The vibration intensity can be controlled within the range of 4.5, the vibration frequency that can be generated is 28Hz, and the amplitude is 3mm, so that the sprayed super absorbent resin can be better dispersed in the high-loft guide layer of the polylactic acid fiber; after leaving the vibrating conveyor curtain, a layer of high-low melting point polylactic acid fiber and super absorbent resin mixture is sprayed again on the surface of the polylactic acid fiber high-loft guide layer, and the spraying amount is 18 grams / square meter, wherein the ratio of high-low melting point polylactic acid fiber: super absorbent resin is: 50:50, wherein the particle size of the super absorbent resin is 35 mesh, and finally the upper layer of dust-free paper is unrolled as the surface layer of the absorbent.

[0080] The above three-layer composite body enters the oven together for heat setting and reinforcement. A three-stage flat-mesh oven is adopted. The heating temperature in the first stage oven is controlled to be 115°C, the heating temperature in the second stage oven is controlled to be 130°C, and the heating temperature in the third stage oven is controlled to be 115°C. After exiting the oven, a three-layer absorption layer is obtained with a gram weight of 206 g / m2.

[0081] The polylactic acid fiber spunlace nonwoven fabric has a gram weight of 35 g / m 2 The high melting point polylactic acid fiber used is a water-repellent fiber with a surface oil content of 0.07%. The melting point of the high melting point single-component polylactic acid fiber is 160-175 degrees.

[0082] For low melting point polylactic acid fiber and high and low melting point polylactic acid two-component fiber, Lurol PP-14160 hydrophilic oil is specially added to the spinning oil during the spinning process, which has the function of single-point multiple hydrophilization and fast water penetration. The surface oil content of low melting point polylactic acid fiber is controlled to be 0.05%, and the surface oil content of high and low melting point polylactic acid fiber is 0.14%. The different oil content is mainly to make the single component polylactic acid fiber produce better melt bonding in the subsequent processing process.

[0083] In the above, the polylactic acid fiber high-loft guide layer is a guide layer with an invention patent owned by Suzhou Jinquan New Materials Co., Ltd. Specifically, it is a guide layer material with a high degradation rate and a preparation method thereof, with patent authorization number: ZL201710096961.0. The super absorbent resin used in the absorbent core layer is a biodegradable absorbent resin of Formosa Plastics Corporation, model BC706, with a biodegradability rate of 66% (180 days).

[0084] The bottom layer is a composite film of polylactic acid fiber spunlace nonwoven fabric and a degradable polylactic acid modified film with polylactic acid as the main component, the modified component is PHA, PBHA, PBS, etc., preferably PHA, and the bottom film with polylactic acid as the main component is produced by Fujian Green Grid Biodegradable Co., Ltd. The weight of the polylactic acid fiber spunlace nonwoven composite film is 60 g / m2.

[0085] Since diapers are a composite of multiple materials, there are also non-woven fabrics for leakproof hems and elastic waistbands. The leakproof hems can be made of polylactic acid fiber spunlace non-woven composite film with a gram weight of 40 g / m2, and the non-woven fabrics for elastic waistbands are polylactic acid spunbond non-woven fabrics (polylactic acid spunbond non-woven fabrics are produced by Shanghai Jingfa Industrial Co., Ltd.) with a gram weight of 35 g / m2. Other components include hot melt adhesive, waist stickers, magic buckles and elastic bands, which can be ignored because they only account for about 10.5%.

[0086] Biodegradable diapers include 100% polylactic acid fiber hot air non-woven fabric, an absorbent core layer material with polylactic acid as the main component, a polylactic acid fiber spunlace non-woven composite film, polylactic acid leak-proof separators and polylactic acid spunbond non-woven elastic waist. The above materials are processed by conventional diaper production equipment to become biodegradable diapers.

[0087] Embodiment 3

[0088] The biodegradable diaper involved in this embodiment includes a diaper body, leak-proof sides, Velcro and an elastic waist; the diaper body includes a surface layer 1, an absorbent core layer 2 and an impermeable bottom film 3; the surface layer 1 is a porous polylactic acid fiber hot air non-woven fabric, and the absorbent core layer 2 includes an upper layer, a middle layer and a lower layer; the upper layer is dust-free paper, the middle layer is a polylactic acid fiber guide layer containing a biodegradable superabsorbent resin, and the lower layer is a polylactic acid fiber spunlace non-woven fabric; the impermeable bottom film 3 is a PHA-modified polylactic acid film.

[0089] The preparation method of the porous polylactic acid fiber hot air nonwoven fabric used in the surface layer 1 of this embodiment is as follows:

[0090] Ordinary hot air cotton production lines are used, such as the hot air cotton production line produced by Changshu Jiuyi High-tech Nonwoven Equipment Co., Ltd. The process flow is made of mixing, coarse opening, cotton blending, fine opening, airflow feeding, carding, web forming and heat setting. Among them, due to the low melting point of single-component polylactic acid fiber, in order to avoid the polylactic acid fiber melting and easy condensation into "corn kernels" and hard hand feel during the opening, carding and heat setting processes, the original PE / PP hot air non-woven fabric production opening, mixing, carding and setting processes are adjusted to reasonably regulate the longitudinal and transverse arrangement directions of the fibers in the fiber web, including various speed ratios of the cylinder and the working roller and stripping roller, the cylinder and the doffer, the condensing roller and the doffer during carding, the control of the draft ratio and the selection of the net quantity. A special process scheme of large gauge, low draft, low speed, light basis weight, weak combing, low tension and multi-stage shaping is adopted to further reduce excessive friction and thermal embrittlement of the fibers. The low-melting point single-component polylactic acid fibers and high-low melting point polylactic acid two-component fiber hot air non-woven fabrics produced have correct fiber arrangement direction, many pores and irregular pore distribution, and have a three-dimensional structure. The fiber webs ensure uniformity, thickness, basis weight and longitudinal and transverse strength ratio requirements of the fiber webs. The low-melting point single-component polylactic acid fibers and high-low melting point polylactic acid two-component fibers are in a ratio of 45:55.

[0091] The main process parameters are: the beater speed of the cotton opener is controlled at 250r / min during opening, the cotton is mixed by horizontal laying and direct taking during the mixing process, so as to achieve the purpose of fully mixing the low-melting-point polylactic acid fiber and the high- and low-melting-point polylactic acid fiber, the speed of the cotton averaging roller is controlled at 180r / min during cotton discharge, the speed of the cotton opener is controlled at 550r / min during fine opening, the air pressure of the air pressure cotton box is controlled at 3MPa in the airflow feeding process, the speed of the mixing roller of the air pressure cotton box is controlled at 310r / min, the speed of the cotton discharge roller is controlled at 18.2-rev / min, the cylinder line speed is adjusted to 610m / min in the combing process, the working roller line speed is controlled to 42.5m / min, the stripping roller line speed is 120.3m / min, the doffer speed is controlled to 20.5m / min, and the weight of the single-layer fiber web formed after stripping by the condensation roller and the cotton stripping roller is 15.4g / m2. The shaping process is carried out in a four-stage flat-net oven. The shaping temperatures of the four-stage oven are controlled at 100°C, 125°C, 120°C, and 110°C respectively. The running speed of the fiber web in the oven is 70 m / min. The weight after leaving the oven is 30.8 g / m 2 Low melting point single component polylactic acid fiber and high and low melting point polylactic acid two-component fiber hot air non-woven fabric.

[0092] In the above, the low melting point polylactic acid fiber and the high and low melting point polylactic acid fiber are specially developed and produced by Suzhou Jinquan New Materials Co., Ltd., wherein the high and low melting point polylactic acid two-component fiber cortex is a modified polylactic acid component, and the modified components include biodegradable materials such as PHA, PBT, PBS, PBAT, PCL, etc. The preferred modified component in the present invention is PHA+PBS. In addition, the low melting point single-component polylactic acid fiber is also a modified fiber, and the modified components include biodegradable materials such as PHA, PBT, PBS, PBAT, PCL, etc. The preferred modified component is PHA, and the modified fiber ratio is PLA:PHA=80:20.

[0093] Among them, the melting point of low melting point polylactic acid fiber is 118-135℃, the core layer of high and low melting point polylactic acid fiber is high melting point polylactic acid component, wherein the melting point of the core layer is 160-175℃, and the skin layer is low melting point component, with a melting point of 118-135℃.

[0094] The absorbent core layer 2 comprises an upper layer, a middle layer and a lower layer. The upper layer is dust-free paper, the middle layer is a polylactic acid fiber guide layer containing biodegradable super absorbent resin, and the bottom layer is a polylactic acid fiber spunlace non-woven fabric.

[0095] The surface dust-free paper is selected with a gram weight of 40g / m2, and the dust-free paper is a heat-sealed dust-free paper, which contains a fiber ratio of wood pulp fiber: high-low melting point polylactic acid bicomponent fiber = 85:25, wherein the high-low melting point polylactic acid bicomponent fiber is 6mm long and has a curl of 0. The dust-free paper is produced by Jiaxing Shenxin Nonwoven Co., Ltd.

[0096] During production, the lower layer of polylactic acid spunlace nonwoven fabric is unrolled first, and a layer of high-low melting point polylactic acid fiber and super absorbent resin mixture is sprayed on it, with a spraying amount of 50 g / m2, wherein the ratio of high-low melting point polylactic acid fiber: super absorbent resin is: 1.5:98.5, wherein the particle size of super absorbent resin is 90 mesh; the polylactic acid fiber high-loft guide layer material is unrolled and laid on the surface of the high-low melting point polylactic acid bicomponent fiber and super absorbent resin mixture, and then super absorbent resin is sprayed on it, with a spraying amount of 80 g / m2, wherein the particle size of super absorbent resin is 70 mesh, and the sprayed lower layer of polylactic acid spunlace nonwoven fabric and polylactic acid fiber high-loft guide layer are sent to the upper driven by the transmission device together, On the lower reciprocating vibrating conveyor curtain, the conveyor curtain generates vibration through the exciting force generated by the eccentric mechanism driven by the motor, and its vibration intensity can be controlled within the range of 6, the vibration frequency that can be generated is 30Hz, and the amplitude is 4mm, so that the sprayed super absorbent resin can be better dispersed in the high-loft guide layer of the polylactic acid fiber; after exiting the vibrating conveyor curtain, a layer of high-low melting point polylactic acid two-component fiber and super absorbent resin mixture is sprayed again on the surface of the polylactic acid fiber high-loft guide layer, and the spraying amount is 30g / m2, wherein the ratio of high-low melting point polylactic acid fiber: super absorbent resin is: 50:50, wherein the particle size of the super absorbent resin is 40 mesh, and finally the upper layer of dust-free paper is unrolled as the surface layer of the absorbent.

[0097] The above three-layer composite body enters the oven together for heat setting and reinforcement. A three-stage flat-mesh oven is adopted. The heating temperature in the first stage oven is controlled to be 120°C, the heating temperature in the second stage oven is controlled to be 140°C, and the heating temperature in the third stage oven is controlled to be 120°C. After exiting the oven, a three-layer absorption layer is obtained with a gram weight of 240 g / m2.

[0098] The polylactic acid fiber spunlace nonwoven fabric has a gram weight of 40g / m2 and uses high melting point single component polylactic acid fiber, which is water repellent and has a fiber surface oil content of 0.08%. The melting point of the high melting point single component polylactic acid fiber is 160-175 degrees.

[0099] For low melting point single component polylactic acid fiber and high and low melting point polylactic acid bicomponent fiber, Lurol PP-14160 hydrophilic oil is specially added to the spinning oil during the spinning process, which has the function of single point multiple hydrophilization and fast water penetration. The surface oil content of low melting point single component polylactic acid fiber is controlled to be 0.08%, and the surface oil content of high and low melting point polylactic acid bicomponent fiber is 0.15%. The different oil content is mainly to make the single component polylactic acid fiber produce better melt bonding in the subsequent processing process.

[0100] In the above, the polylactic acid fiber high-loft guide layer is a guide layer with an invention patent owned by Suzhou Jinquan New Materials Co., Ltd. Specifically, it is a guide layer material with a high degradation rate and a preparation method thereof, with patent authorization number: ZL201710096961.0. The super absorbent resin used in the absorbent core layer is a biodegradable absorbent resin of Formosa Plastics Corporation, model BC706, with a biodegradability rate of 66% (180 days).

[0101] The anti-seepage bottom film 3 is a composite film of polylactic acid fiber spunlace nonwoven fabric and a degradable polylactic acid modified film with polylactic acid as the main component, the modified component is PHA, PBHA, PBS, etc., preferably PHA, and the bottom film with polylactic acid as the main component is produced by Fujian Green Grid Biodegradable Co., Ltd. The weight of the polylactic acid fiber spunlace nonwoven composite film is 65 g / m2.

[0102] Since diapers are a composite of multiple materials, there are also non-woven fabrics for leakproof hems and elastic waistbands. The leakproof hems can be made of polylactic acid fiber spunlace non-woven composite film with a gram weight of 40 g / m2, and the non-woven fabrics for elastic waistbands are polylactic acid spunbond non-woven fabrics (polylactic acid spunbond non-woven fabrics are produced by Shanghai Jingfa Industrial Co., Ltd.) with a gram weight of 35 g / m2. Other components include hot melt adhesive, waist stickers, magic buckles and elastic bands, which can be ignored because they only account for about 10.5%.

[0103] Biodegradable diapers include 100% polylactic acid fiber hot air non-woven fabric, an absorbent core layer material with polylactic acid as the main component, a polylactic acid fiber spunlace non-woven composite film, polylactic acid leak-proof separators and polylactic acid spunbond non-woven elastic waist. The above materials are processed by conventional diaper production equipment to become biodegradable diapers.

[0104] The main properties of the polylactic acid fiber hot air non-woven fabric surface layer and the prepared degradable diapers in the above examples were tested:

[0105] The test items include the antibacterial property, air permeability, moisture conductivity, pH value of the surface of polylactic acid fiber hot air non-woven fabric, the degradation performance and water absorption rate of degradable diapers; the specific test methods are as follows:

[0106] Antibacterial property: GB15979-2002 (hygienic standard for disposable sanitary products).

[0107] Air permeability: Tested according to GB / T5453-1997 standard. Adjust the test pressure difference to 60Pa and select a nozzle diameter of 7mm.

[0108] Moisture conductivity: Tested according to ZB W 04019-1990 standard. Test fabric sample size 25mm*300mm, measure water absorption height in 60s.

[0109] pH value: Tested according to the method specified in Appendix C of GB / T 8939-2008.

[0110] Water absorption rate: tested according to the method specified in GB / T 8939-2008 standard.

[0111] Penetration performance: refer to Appendix A of GB / T 28004-2011.

[0112] Degradability: Evaluated according to the method and conditions of GB / T19277-2003 (IDT ISO 14855:1999).

[0113] Test results: see Table 1

[0114] Table 1: Performance test of biodegradable diapers

[0115]

[0116] Taking Example 1 as an example, the prepared diaper was subjected to a degradation experiment. Figures 11 to 16 It can be seen that after thirteen weeks of degradation experiment, all of them turned into fragments smaller than 10mm, and the degradation experiment was successful.

[0117] Degradation test results of diapers of the present invention

[0118]

[0119] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A biodegradable diaper, characterized in that: It includes a diaper body, leak-proof sides, Velcro and an elastic waist; the diaper body includes a surface layer, an absorbent core layer and an impermeable bottom film; The surface layer is a porous polylactic acid fiber hot air nonwoven fabric, and the absorbent core layer includes an upper layer, a middle layer and a lower layer; the upper layer is dust-free paper, the middle layer is a polylactic acid fiber guide layer containing a biodegradable super absorbent resin, and the lower layer is a polylactic acid fiber spunlace nonwoven fabric; The anti-seepage bottom membrane is a PHA modified polylactic acid membrane.

2. The biodegradable diaper according to claim 1, characterized in that: The PLA:PHA ratio in the PHA modified polylactic acid film is 3-7:7-3.

3. The biodegradable diaper according to claim 1, characterized in that: The polylactic acid fiber hot air non-woven fabric is composed of low-melting point polylactic acid fibers and high- and low-melting point polylactic acid fibers mixed in a weight ratio of 25-45:55-75, wherein the low-melting point polylactic acid fibers have a specification of 1.5-3.0D*38mm, and the high- and low-melting point polylactic acid fibers have a specification of 1.0-2.0D*38mm; the core layer of the high- and low-melting point polylactic acid fibers is a high-melting point polylactic acid component, and the skin layer is a low-melting point polylactic acid component or a modified polylactic acid component; the low-melting point polylactic acid fibers are modified polylactic acid components.

4. The biodegradable diaper according to claim 3, characterized in that: The modified component used in the modified polylactic acid component includes at least one of PHA, PBT, PBS, PBAT or PCL.

5. The biodegradable diaper according to claim 3, characterized in that: The preparation process of the polylactic acid fiber hot air nonwoven fabric is as follows: When opening, the beater speed of the cotton opener is controlled to be 250-380r / min. During the mixing process, the cotton is mixed by horizontal spreading and direct taking. When discharging cotton, the speed of the cotton roller is controlled to be between 180-220r / min. During fine opening, the speed of the cotton opener is controlled to be 550-680r / min. In the airflow feeding process, the air pressure of the air box is controlled to be between 3-4.8MPa, and the speed of the mixing roller of the air box is controlled to be between 310-430r / min. The speed of the cotton outlet roller is 18.2-25.5 rpm. During the carding process, the cylinder line speed is adjusted to 610-750m / min, the working roller line speed is controlled to 42.5-58.9m / min, the stripping roller line speed is 120.3-141.2m / min, and the doffer speed is controlled to 20.5-30.6m / min. The weight of the single-layer fiber web formed after stripping by the condensing roller and the stripping roller is 9.8-15.4g / m2. The shaping process is carried out in a four-stage flat-net oven, and the shaping temperatures of the four-stage oven are controlled at 100-110 degrees, 125-135 degrees, 120-130 degrees, and 110-120 degrees respectively. The running speed of the fiber web in the oven is 70-80mi / min. After leaving the oven, a polylactic acid fiber hot air non-woven fabric with a gram weight of 19.6-30.8g / m2 is obtained, which is composed of low-melting-point polylactic acid fibers and high and low-melting-point polylactic acid fibers.

6. The biodegradable diaper according to claim 1, characterized in that: The preparation process of the absorbent core layer is as follows: First, the polylactic acid spunlace nonwoven fabric used in the lower layer is unwound, and a layer of a mixture of high and low melting point polylactic acid fibers and super absorbent resin is sprayed on it, with a spraying amount of 30-50 g / m2, wherein the ratio of high and low melting point polylactic acid bicomponent fibers: super absorbent resin is: 0.5-1.5:98.5-99.5, wherein the particle size of super absorbent resin is 80-90 mesh; The polylactic acid fiber high-loft guide layer material is unwound and laid on the surface of the high-low melting point polylactic acid fiber and super absorbent resin mixture, and then the super absorbent resin is sprayed thereon, and the spraying amount is 70-80 g / m2, wherein the particle size of the super absorbent resin is 60-70 meshes, and the sprayed lower layer of polylactic acid spunlace non-woven fabric and the polylactic acid fiber high-loft guide layer are sent together to the upper and lower reciprocating vibration conveying long curtains driven by the transmission device, and the conveying long curtain is driven by the eccentric mechanism driven by the motor to generate an exciting force to generate vibration, and the vibration intensity can be controlled in the range of 3-6, and the vibration frequency that can be generated is 25-30Hz, and the amplitude is 2-4mm, so that the sprayed super absorbent resin is better dispersed in the polylactic acid fiber high-loft guide layer; After exiting the vibrating conveyor curtain, a layer of high-low melting point polylactic acid double fiber and super absorbent resin mixture is sprayed again on the surface of the polylactic acid fiber high-loft guide layer, with a spraying amount of 15-30 g / m2, wherein the ratio of high-low melting point polylactic acid fiber: super absorbent resin is 50:50, and the particle size of super absorbent resin is 30-40 mesh; Finally, the dust-free paper is unrolled as the upper layer of the absorbent; The three layers after stacking are put into the oven together for heat setting and reinforcement. A three-stage flat-net oven is used. The heating temperature in the first stage oven is controlled to be 110-120°C, the heating temperature in the second stage oven is controlled to be 120-140°C, and the heating temperature in the third stage oven is controlled to be 110-120°C. After exiting the oven, a three-layer absorption layer is obtained with a gram weight of 180-240 g / m2. The polylactic acid fiber spunlace nonwoven fabric has a gram weight of 30-40g / m2, and the polylactic acid fiber used is a water-repellent fiber with a surface oil content of 0.06-0.08%. The melting point of the high-melting-point polylactic acid fiber is 160-175 degrees.

7. The biodegradable diaper according to claim 6, characterized in that: During the spinning process of the low-melting-point polylactic acid fiber and the high-low-melting-point polylactic acid fiber, the surface oil used is added with Lurol PP-14160 hydrophilic oil agent.

8. The biodegradable diaper according to claim 7, characterized in that: The surface oil content of the low melting point polylactic acid fiber is 0.02-0.08%, and the surface oil content of the high and low melting point polylactic acid fiber is 0.12-0.15%.

Citation Information

Patent Citations

  • Anti-side leakage degradable polylactic acid sanitary napkin and preparation method thereof

    CN104096258A

  • Polylactic acid fiber diversion layer material and preparing method thereof

    CN106894160A

  • High-degradation rate diversion layer material and preparing method thereof

    CN106974768A

  • Water absorption core and preparation method and application thereof

    CN109620546A

  • Degradable composite absorption core, preparation method thereof and application thereof in paper diapers

    CN111920587A

Cited By

  • Polylactic acid two-component composite fiber and degradable absorption core body prepared from polylactic acid two-component composite fiber

    CN119287536A

  • A polylactic acid bicomponent composite fiber and a degradable absorbable core prepared by the same

    CN119287536B